(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study of the role of the industrial sector in protecting and testing the Iraqi environment is one of the important matters and issues in diagnosing the path of the economy towards achieving sustainable development. The study shows the negative effects of the productive processes that occur in this sector. Our study was based on the hypothesis that "the industrial sector has a weak role in the process of protecting the environment in Iraq, and industrial investments have not adopted the environmental dimension at the level of the environmental problem in their accounts when making the investment. Depending on the methodology of descriptive and inductive analysis, through a study of the Iraqi industrial sector And testing its role in protecting the environment, and working on the use of scientific books and statistical publications to achieve the goal of the study and knowing the validity of the hypothesis or not. The study concluded that many Iraqi industries were originally established on the basis of traditional production and not under the umbrella of a clean environment, and it was necessary to strengthen the role of these industries in the economic and environmental fields. Also, it is necessary to re-evaluate existing industrial projects from an environmental point of view, and to introduce environmental feasibility studies for modern industrial investments, and to obligate everyone to the Iraqi environmental determinants, conditions and specifications.